Rethinking domestic violence : the social work and probation response - Mullender, Audrey (Routledge, 1996)
Annotation This book explodes the myths concerning domestic violence and explores how the responses of social workers and probation officers to the people involved need to be far better coordinated and more effective.
Keywords: Wife abuse -- Great Britain.; Abused women -- Counseling of -- Great Britain.; Abused wives -- Counseling of -- Great Britain.; Social work with women -- Great Britain.; Family violence -- Great Britain -- Prevention.; Abusive men -- Counseling of -- Great Britain.; Abusive men -- Rehabilitation -- Great Britain.; Probation -- Great Britain.; Domestic Violence; Spouse Abuse; United Kingdom; Femmes -- Violence envers -- Grande-Bretagne.; Femmes victimes de violence -- Counseling -- Grande-Bretagne.; Service social aux femmes -- Grande-Bretagne.; Probation (Droit) -- Grande-Bretagne.; Violence conjugale.; FAMILY & RELATIONSHIPS -- Abuse -- Elder Abuse.; FAMILY & RELATIONSHIPS -- Abuse -- Domestic Partner Abuse.; Abused wives -- Counseling of; Abused women -- Counseling of; Abusive men -- Counseling of; Abusive men -- Rehabilitation; Family violence -- Prevention; Probation; Social work with women; Wife abuse; Great Britain